The Impact of Coal Price, Global Oil, and Macroeconomic Indicators on Coal Subsector Stock Prices - Agung, Dewawngga Amarta; Galuh, Ajeng Kartika (Contemporary Studies in Economic, Finance and Banking, 2025)
This study investigates the impact of coal benchmark prices (HBA), global oil prices (HMD), inflation, and interest rates on the stock prices of coal sub-sector companies listed on the Indonesia Stock Exchange during 2019–2023. The urgency of this research lies in the absence of recent empirical studies during a period marked by significant energy and macroeconomic fluctuations. Employing a panel data regression with a Random Effect Model (REM), the findings reveal that HBA, HMD, and interest rates positively and significantly affect coal stock prices, while inflation exerts a significant negative influence. These findings reinforce the Arbitrage Pricing Theory (APT), which explains that macroeconomic variables and commodities systematically impact stock valuation. The study contributes practical implications for investors and policymakers to formulate adaptive strategies in the dynamic commodity and financial markets.